Pengaruh Online Customer Review Dan Perceived Risk Terhadap Keputusan Pembelian : (Studi Pada Konsumen Sociolla Kota Medan) - Karin Aurani; Nana Dyki Dirbawanto (Jurnal Manajemen Bisnis Era Digital, 2024)
Currently, the beauty care industry is experiencing significant sales growth. However, in 2022, the number of monthly web visits to Sociolla decreased. High perceived risk can make consumers hesitant to make purchases. Similarly, online customer reviews can greatly impact consumer confidence. This study aims to determine the effect of online customer reviews and perceived risk on purchasing decisions for Sociolla consumers in Medan city. The research employed a quantitative approach with an associative design. The study focused on Sociolla application users in Medan City, with a sample size of 96 respondents selected through non-probability purposive sampling. Primary data was collected through direct distribution of questionnaires, while secondary data was obtained through literature review. The study results suggest that online customer reviews have a significant positive impact on purchasing decisions. The t-count value of 4.478 (>1.985) and a significance value of 0.000 (<0.05) indicate this. Additionally, perceived risk also has a significant positive effect on purchasing decisions, with a t-count value of 2.049 (>1.985) and a significance value of 0.043 (<0.05), and a regression coefficient value of 0.134. During simultaneous testing, the variable of online customer reviews and perceived risk have a combined effect with a level of influence of 21.3%. The remaining 78.7% is influenced by factors outside the scope of this study.